Sport as power of integration among minorities - Faragó , Beatrix; Béki , Piroska (Applied Studies in Agribusiness and Commerce, 2015)
The opportunities and development of skills in the field of sports may open a door to social inclusion that also facilitates social integration. Based on the funding provided by the national sports strategy and integration, the research project can be developed further on and implemented. The efforts of the European Union (EU) and of the European Council towards the member states are carried out through its directives, and the analyses of these documents provide guidelines for the elaboration of the Hungarian Roma strategies. Funding is one of the key factors for the elaboration of Roma integration strategy and its efficiency. The research highlights upon the way of thinking and mentality of Roma young people about sports currently, and on the importance of sport affairs for them. Also, reflects on the factors which promote motivation to have successful career goals and achieve those based on the program. The sports integration survey suggests conclusions on the role of mentoring in Roma youngsters’ studies, in sports, in building social relations, the role model motivating for them, or on the supportive role of the parents or even the lack of it in their families. The expected result would be a survey on sporting habits of the Roma minority and disadvantaged youth and their positioning in education through which we could develop programs to promote the integration of the Roma minority and to improve their general circumstances. The National Social Inclusion Strategy (Ministry of Human Capacities, National Social Inclusion Strategy 2011–2020) provides the financial background of the integration project whose application also prevails in the field of sports integration. The aspirations of the EU provide guidance to the amount of funding and its allocation manners. The National Roma Self-Government’s (NRSG) sports integration project and best practice has provided the basis for the sports integration research project. The survey is examining the recreational habits, motivational factors, study levels among the Roma minority and the disadvantaged young people. Based on the questionnaire, we can draw some conclusions about the development of sports integration programs. The issues cover the field of sport activities of young people aged between 9-18 and on the significance of sport opportunities for break-out for the Roma youth, and on the effect of role models for them. The sports integration projects treat simultaneously the development of education and sport, furthermore they are significantly linked to each other. The target group of the questionnaire survey are mainly the Roma and disadvantaged people. The sample item number is 1216 completed questionnaires from the whole territory of the country, from 16 schools. As shown in the survey, the sport and the level of education are significantly related to each other. Those who do any sports, obtain higher level of achievement in their studies. It can be revealed by the fact that through mentoring the sportsmen can promote their school performance and sport development together. The research highlights on another observation, namely, it also confirms the legitimacy of sports integration program and points out the direction for development. For accomplishing the goal of social inclusion through sport we have at hand the appropriate concept. It is, furthermore necessary to strengthen and to develop the mentoring program, which ensures the lower drop-out rate among the participants. The effect of Sports integration is motivating for the Roma and for the disadvantaged youth. The use of sport as a tool for social inclusion proves to be of utmost importance. JEL code: Z23